Change trend and gender differences in disability-free life expectancy among older adults in China, 2010–2020 - Lu, Min; Wang, Xuehui; Shen, Kaijun; Ji, Chengpeng; Li, Wenxia (Frontiers in Public Health, 2023)
Objective The goal of the present study was to investigate gender differences in disability-free life expectancy (DFLE) and DFLE/LE ratio among older adults in China; portray changing trend from 2010 to 2020; and discuss the implications for public policies. Methods Mortality data and disability rate data were derived from the Sixth China Population Census in 2010 and the Seventh China Population Census in 2020. The study assessed disability status of older adults based on self-assessment health in the above censuses. Life table and Sullivan method were used to estimate LE, DFLE, and DFLE/LE ratio by gender. Results DFLE increased from 19.33 to 21.78 years for 60-year-old males, while from 21.94 to 24.80 years for 60-year-old females, from 2010 to 2020, respectively. DFLE/LE ratio was 96.40% for 60-year-old males and 94.86% for 60-year-old females in 2010, while DFLE/LE ratio was 96.63% for 60-year-old males and 95.44% for 60-year-old females in 2020, respectively. In terms of gender differences in DFLE/LE ratio, men aged 60 are 1.19 percentage points higher than women at the same age; men aged 70 are 1.71 percentage points higher than women; men aged 80 are 2.87 percentage points higher than women. Conclusion From 2010 to 2020, the DFLE of China’s male and female older adults increased simultaneously with the increase of LE, and the DFLE/LE ratio also increased. However, the DFLE/LE ratio of female older adults is lower than that of male at the same age, and this gender difference is narrowing over the decade but has not yet been eliminated, especially the health disadvantage of female older adults among the oldest old age group (age 80 and above) is more prominent.